Identification of two QTLs associated with high fruit acidity in apple using pooled genome sequencing analysis - Ban, Seunghyun (Hortic Res, 2020)
Acidity is a critical component determining apple fruit quality. Previous studies reported two major acidity quantitative trait loci (QTLs) on linkage groups (LGs) 16 (Ma) and 8 (Ma3), respectively, and their homozygous genotypes mama and ma3ma3 usually confer low titratable acidity (TA) (<3.0 mg ml(−1)) to apple fruit. However, apples of genotypes Ma- (MaMa and Mama) or Ma3- (Ma3Ma3 and Ma3ma3) frequently show an acidity range spanning both regular (TA 3.0–10.0 mg ml(−1)) and high (TA > 10 mg ml(−1)) acidity levels. To date, the genetic control for high-acidity apples remains essentially unknown. In order to map QTLs associated with high acidity, two genomic DNA pools, one for high acidity and the other for regular acidity, were created in an interspecific F(1) population Royal Gala (Malus domestica) × PI 613988 (M. sieversii) of 191 fruit-bearing progenies. By Illumina paired-end sequencing of the high and regular acidity pools, 1,261,640 single-nucleotide variants (SNVs) commonly present in both pools were detected. Using allele frequency directional difference and density (AFDDD) mapping approach, one region on chromosome 4 and another on chromosome 6 were identified to be putatively associated with high acidity, and were named Ma6 and Ma4, respectively. Trait association analysis of DNA markers independently developed from the Ma6 and Ma4 regions confirmed the mapping of Ma6 and Ma4. In the background of MaMa, 20.6% of acidity variation could be explained by Ma6, 28.5% by Ma4, and 50.7% by the combination of both. The effects of Ma6 and Ma4 in the background of Mama were also significant, but lower. These findings provide important genetic insight into high acidity in apple.